2020
DOI: 10.1111/tbed.13520
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and evolutionary analysis of HoBi‐like pestivirus: Insights into origin and dispersal

Abstract: The HoBi‐like pestivirus (HoBiPeV), currently classified as Pestivirus H species, is a pathogen associated with a broad spectrum of clinical manifestations in ruminants, particularly in cattle. Since HoBiPeV complete genome sequencing data is scarce, in the present study we described five nearly complete new Brazilian HoBiPeV genomes and further perform a more complete genetic and evolutionary characterization with all additional genome sequences available in the GenBank database. Entropy and selection pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 31 publications
1
22
2
Order By: Relevance
“…There are only a handful of molecular dating estimates for pestiviruses and they mostly focus on viral species or clades that are associated with economic losses. Diversification of bovine viral diarrhea virus 1 (Pestivirus A) subtypes was estimated to have started about 363 years ago (Weber et al, 2021), and the divergence of HoBi-like pestivirus (Pestivirus H) was dated back to the 16 th century (Silveira et al, 2020). Our results provide the first robust ancient time node for pestiviruses based on the estimated EVEs integration date and suggest that pestiviruses were already circulating in mammals more than 10.8 million years ago.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a handful of molecular dating estimates for pestiviruses and they mostly focus on viral species or clades that are associated with economic losses. Diversification of bovine viral diarrhea virus 1 (Pestivirus A) subtypes was estimated to have started about 363 years ago (Weber et al, 2021), and the divergence of HoBi-like pestivirus (Pestivirus H) was dated back to the 16 th century (Silveira et al, 2020). Our results provide the first robust ancient time node for pestiviruses based on the estimated EVEs integration date and suggest that pestiviruses were already circulating in mammals more than 10.8 million years ago.…”
Section: Discussionmentioning
confidence: 99%
“…Although several regions of pestivirus genome have been used, phylogenetic analyses based on the entire N pro gene sequences or the combined datasets of 5′‐UTR and N pro sequences have been found useful in ascertaining the genotypes or clades within a pestivirus species as they provide increased statistical support (Becher et al., 1997; Liu et al., 2010; Liu, Xia, et al., 2009; Mishra et al., 2014; Silveira et al., 2020). Based on the 5′‐UTR sequences, four lineages or clades (a–d) of HoBiPeV have been reported, while based on complete N pro sequences, three clades (a, c and d) of HoBiPeV have been found thus far (Giammarioli et al., 2015; Mishra et al., 2014; Silveira et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although several regions of pestivirus genome have been used, phylogenetic analyses based on the entire N pro gene sequences or the combined datasets of 5′‐UTR and N pro sequences have been found useful in ascertaining the genotypes or clades within a pestivirus species as they provide increased statistical support (Becher et al., 1997; Liu et al., 2010; Liu, Xia, et al., 2009; Mishra et al., 2014; Silveira et al., 2020). Based on the 5′‐UTR sequences, four lineages or clades (a–d) of HoBiPeV have been reported, while based on complete N pro sequences, three clades (a, c and d) of HoBiPeV have been found thus far (Giammarioli et al., 2015; Mishra et al., 2014; Silveira et al., 2020). Comparison of previously reported HoBiPeV sequences and the HoBiPeV sequences generated in this study revealed emergence of another novel lineage (proposed as HoBiPeV‐e) in India indicating that the currently circulating HoBiPeV strains around the world can be divided into five HoBiPeV lineages (a–e), based on 5′‐UTR sequences and into four lineages (a, c, d and e), on the basis of complete N pro sequences or combined 5′‐UTR‐N pro sequences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations